Influence of Eta-Phase on Wear Behavior of WC-Co Carbides. (3rd January 2016) - Formisano, A.; Capece Minutolo, F.; Caraviello, A.; Carrino, L.; Durante, M.; Langella, A.
Abstract : Cemented carbides, also known as Widia, are hard metals produced by sintering process and widely used in mechanical machining. They show high cutting capacity and good wear resistance; consequently, they result to be excellent materials for manufacturing cutting tools and sandblast nozzles. In this work, the wear resistance of WC-Co carbides containing Eta-phase, a secondary phase present in the hard metals when a carbon content deficiency occurs, is analyzed. Different mixtures of carbide are prepared and sintered, with different weight percentages of carbon, in order to form Eta-phase and then analyze how the carbon content influences the wear resistance of the material. This characterization is carried out by abrasive wear tests. The test parameters are chosen considering the working conditions of sandblast nozzles. Additional information is gathered through microscopic observations and the evaluation of hardness and microhardness of the different mixtures. The analyses highlight that there is a limit of carbon content below which bad sintering occurs. Considering the mixtures without these sintering problems, they show a wear resistance depending on the size and distribution of the Eta-phase; moreover, the one with high carbon content deficiency shows the best performance.